PERSEPSI GURU TERHADAP KOMPETENSI SOSIAL KEPALA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI DI KOTA PARIAMAN - Devi Rahmadani (Jurnal Bahana Manajemen Pendidikan, 2015)
This article describe result of research about teachers perception of the social competence of Head Master of SMK Negeri in Pariaman. The population of this research are 292 civil service teachers and 73 civil service teachers were taken as a sample.Sampling technics were using is Proportional Random Sampling with cochran formula. The instrument used in this research is questionnaire and analyzed by average. In general, the result of this research is teachers perception of the social competence of Head of State Vocational High School in Pariaman City have is good enough at 3,51.Key Words :Social Competence, Head Master, Teachers